2009
DOI: 10.1016/j.molcel.2009.04.020
|View full text |Cite
|
Sign up to set email alerts
|

CUL4A Abrogation Augments DNA Damage Response and Protection against Skin Carcinogenesis

Abstract: SUMMARY It is intuitively obvious that the ability of a cell to repair DNA damage is saturable, either by limitation of enzymatic activities, the time allotted to achieve their function, or both. However, very little is known regarding the mechanisms that establish such a threshold. Here we demonstrated that the CUL4A ubiquitin ligase restricts the cellular repair capacity by orchestrating the concerted actions of nucleotide excision repair (NER) and the DNA damage-responsive G1/S checkpoint through selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
223
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(232 citation statements)
references
References 56 publications
8
223
0
1
Order By: Relevance
“…Among the CUL4 substrates that control cell cycle progression, the cyclin-dependent kinase inhibitor p21 was recently shown to be targeted for ubiquitination and degradation by both CUL4A and CUL4B under normal conditions as well as post-UV irradiation in cell lines [10,11]. However, primary mouse embryonic fibroblasts preferentially utilize CUL4A to restrict p21 levels [12], suggesting context-dependent degradation of p21 by the two CUL4 ubiquitin ligases. Cul4a null mice are viable and display no gross phenotypic abnormalities throughout their lifespan except for meiotic defects in male mice [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the CUL4 substrates that control cell cycle progression, the cyclin-dependent kinase inhibitor p21 was recently shown to be targeted for ubiquitination and degradation by both CUL4A and CUL4B under normal conditions as well as post-UV irradiation in cell lines [10,11]. However, primary mouse embryonic fibroblasts preferentially utilize CUL4A to restrict p21 levels [12], suggesting context-dependent degradation of p21 by the two CUL4 ubiquitin ligases. Cul4a null mice are viable and display no gross phenotypic abnormalities throughout their lifespan except for meiotic defects in male mice [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, primary mouse embryonic fibroblasts preferentially utilize CUL4A to restrict p21 levels [12], suggesting context-dependent degradation of p21 by the two CUL4 ubiquitin ligases. Cul4a null mice are viable and display no gross phenotypic abnormalities throughout their lifespan except for meiotic defects in male mice [12][13][14]. Despite the largely overlapping functions of CUL4A and CUL4B, recent studies also revealed distinct roles for the two CUL4 family members in DNA-damage response, male meiosis, and response to environmental toxins [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CULLIN 4 is known to play an important role in the response to DNA damage. 10 Interestingly, Cullin 4A mutant cells show an increased resistance to UVmediated DNA damage associated with a prolonged DNA repair response as a result of reduced degradation of DNA damage sensors, such as DDB2 and DNA repair protein complementing XP-C (XPC). 10 In light of our results, it is tempting to speculate that CULLIN 4 function may have evolved to temporally limit the induction of different stress pathways.…”
Section: Temporal Regulation Of Autophagy Response By the Cullin 4-ammentioning
confidence: 99%
“…CUL4A and CUL4B assemble structurally similar E3 complexes through binding to an adaptor protein (DDB1) and a substrate receptor protein (DCAF) at the N-terminus, and a RING protein RBX1 at the C-terminus (Figure 1), and share functional redundancy in targeting substrates such as p21 and Cdt1 for ubiquitination and degradation [1,2]. The Cul4a-null mice are viable and display no abnormal development and growth phenotypes, likely due to functional compensation from Cul4b [4,5]. The only phenotype associated with Cul4a abrogation is the reproductive defects seen with male but not female mice, resulting from differential non-overlapping expression patterns of the two Cul4 genes during male meiosis [6].…”
mentioning
confidence: 99%